The role of parental alcohol use, parental discipline and antisocial behaviour on adolescent drinking trajectories - Alati, Rosa; Baker, P.; Betts, K.; Connor, J.; Little, K.; Sanson, A.; Olsson, C. (Elsevier Ireland Ltd, 2014)
Backgrounds: : Parental drinking, harsh parental discipline and adolescent antisocial behaviour have been independently implicated in adolescent alcohol use. Robust prospective studies are required to examine developmental relationships between these factors and their effect on trajectories of alcohol use across adolescence. Methods: Data were ascertained at three consecutive adolescent waves (13.5, 15.5 and 17.5 years) from the Australian Temperament Project, a 15-wave (30 year) general population birth cohort in Victoria, Australia. Adolescent alcohol trajectories, adjusted for time-varying measures of parenting and antisocial behaviour, were regressed on time-stable measures of parental alcohol use. The full case analysis comprised 751 individuals with complete data. Results: Two distinct alcohol trajectories were identified across the three adolescent waves after adjusting for time-varying factors: a higher and lower drinking group. Both trajectories increased linearly over the study period. Antisocial behaviour was positively associated with both trajectories while harsh parental discipline was positively associated with alcohol use in the lower-use group only. Increased maternal and paternal drinking at 13.5 years placed teenagers at a greater risk of being included in the high-risk trajectory. Conclusion: Parental drinking was the strongest predictor of different drinking trajectories in adolescence. This finding underscores the importance of comprehensive public heath approaches that target both parental and adolescent drinking attitudes and behaviour. © 2013 Elsevier Ireland Ltd.